Superparabolic level-glancing models for two-state quantum systems - Lehto J; Suominen KA (AMER PHYSICAL SOC, 2025)
Level crossing models for two-state quantum systems are applicable to a wide variety of physical problems. We address the special case of level glancing, i.e., when energy levels reach a degeneracy at a specific point of time, but never actually cross. The simplest model with such behavior is the parabolic model, and its generalizations, which we call superparabolic models. We discuss their basic characteristics, complementing the previous work on the related nonlinear crossing models [Vitanov and Suominen, Phys. Rev. A 59, 4580 (1999)].